Persistent Mixed Donor Chimerism following Double Umbilical Cord Transplantation in a Patient with T-Cell Prolymphocytic Leukemia - Ronak H. Mistry; Elizabeth O. Hexner; James K. Mangan (Case Reports in Hematology)
T-cell prolymphocytic leukemia (T-PLL) is a rare and aggressive postthymic T-cell neoplasm with an associated survival time of 1 year when left untreated. Current standard of care for T-PLL is with alemtuzumab, followed by allogeneic or autologous stem cell transplant. Little is found in the literature about alternative donor transplantation in T-PLL. Here, we present the case of a patient treated with double umbilical cord blood transplantation, which resulted in initial complete remission. An unusual outcome of this case is that coengraftment of both cords was established. After 16 months, the patient had relapse of the disease, unfortunately, prompting treatment with alemtuzumab and pentostatin, which resulted in remission once again. Here, we report a unique phenomenon whereby single-cord dominance occurred after treatment with these agents, suggesting that anti-T-cell therapy after transplant may help achieve single-unit dominance. A second relapse of the disease occurred six months thereafter, ultimately resulting in the patient’s death, highlighting the aggressive nature of this disease.